Optimization Method of Generation Rights Transaction Mechanism for Power System Accommodation Improvement - Haoliang XU; Panrun JIN; Jiheng JIANG; Zongxiang LU; Ying QIAO (Zhongguo dianli)
With renewable energy consumption becoming a key issue, generation rights transaction between wind power and captive plants plays an important role in improving the power system's accommodation capacity. But there is no theory for evaluating and optimizing such mechanisms in the medium and long term. Based on probabilistic production simulation, this paper proposes a medium and long-term evaluation model to calculate system’s accommodation capacity rapidly. The main factors affecting accommodation effect are summarized after analysis of operation mode of generation rights transaction. Considering the probabilistic characteristics of load and various power sources, an assessment model is constructed. Then, the shaping effect of the power generation rights transaction on the wind power probability curve is discussed, followed by analyzing the relationship between wind curtailment reduction and three key parameters: transaction capacity, start-up wind power and daily transaction time. The simulation results validate the effectiveness of the proposed algorithm in quick optimization and efficiency evaluation in monthly and annual scale.